Vasculitis: an update. - Luqmani, R (MA Healthcare Ltd, 2014)
The systemic vasculitides are uncommon but serious diseases. Early recognition can be difficult because they mimic many conditions. Aggressive immunosuppression is toxic but effective; a targeted approach with biological agents may improve the outcome.